1980
DOI: 10.1192/bjp.137.1.26
|View full text |Cite
|
Sign up to set email alerts
|

ECT: III: Enduring Cognitive Defecits?

Abstract: Cognitive function was compared in carefully matched groups of ECT and non-ECT treated depressives and in matched normal volunteer controls on admission, at 4 months and at 7 months. ECT caused little impairment at 4 months and no impairment at 7 months on a comprehensive cognitive test battery. Severity of depression had a marked effect on cognitive function. Within the ECT group bilateral ECT caused more impairment than unilateral ECT one week after a course but 3 months later the differences had disappeared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
2

Year Published

1986
1986
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(38 citation statements)
references
References 30 publications
2
34
0
2
Order By: Relevance
“…Furthermore, the memory disturbance of the untreated, depressed patient is a diminished acquisition of new information, whereas ECT causes a transient disruption of the retention of new information with unchanged or even increased acquisition. Once the series of ECT is completed, the capacity for new learning and retention, which depends on an intact hippocampal function, recovers in about 72 days (Weeks et al 1980). The long-term effect of ECT in depression is, therefore, not compromised by the reversible treatmentinduced memory disruption.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, the memory disturbance of the untreated, depressed patient is a diminished acquisition of new information, whereas ECT causes a transient disruption of the retention of new information with unchanged or even increased acquisition. Once the series of ECT is completed, the capacity for new learning and retention, which depends on an intact hippocampal function, recovers in about 72 days (Weeks et al 1980). The long-term effect of ECT in depression is, therefore, not compromised by the reversible treatmentinduced memory disruption.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, electrode position, energy, and type of current have been related with the degree of cognitive impairments. Specifically, some of them (Weeks et al 1980;Squire and Chace 1996;Sackeim et al 2008) have found that unilateral right positions have less severe cognitive effects than bilateral positions, which support previous review studies (Squire 1977;Calev et al 1995;Squire and Chace 1996). Sackeim et al (2008) in a double-blind study investigate the effects of different electrode placement (bilateral vs. right unilateral) and pulse width (0.3 vs. 1.5 ms) and found that the ultrabrief right unilateral group had less cognitive side effects than the other groups.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding electrical dosage, Sackeim et al (2000) compared different electrode position (bilateral vs. right unilateral) and electric dosage (50% vs. 150% and 500% above the seizure threshold) and found that a high dosage result in a greater cognitive impairment. Most of these studies have also shown that both learning and retaining were totally recovered between a few weeks and 7 months after the ECT series (Weeks et al 1980;Frith et al 1983;Calev et al 1991;Squire and Chace 1996). Moreover, Zervas et al (1993) associated patient age in adults to the risk of short-term memory deficits in patients treated with ECT.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, it may contribute to the transient cognitive impairment that accompanies ECS in humans. 31) Electrophysiological changes in granule cell neurons by ECS treatment were also examined. 32,33) Chronic ECS treatments enhance baseline levels of synaptic transmission in the dentate gyrus.…”
Section: Morphological and Functional Changes In Mature Neurons Of Dementioning
confidence: 99%